Connecting with close friends online: A qualitative analysis of young adults’ perceptions of online and offline social interactions with friends - Riley A. Scott; Jaimee Stuart; Bonnie L. Barber (Computers in Human Behavior Reports, 2022)
Despite recognition that the internet is a critical context for friendships among youth, little is known about whether young adults perceive differences in their interactions with close friends across online and offline (i.e., face-to-face) settings. The current study sought to address this gap by qualitatively investigating young adults’ perceptions of how their social interactions with friends differ across online and offline contexts. A large sample of Australian young adults (N = 687; 59.8% female; Mage = 19.45 years, SD = 2.07) were recruited for the study. The overall corpus of data analyzed included 672 responses to the open-ended question: “How do you think your interactions with your close friends online differ compared to interactions with them offline (i.e., face-to-face)?” Analyses identified 567 participants who perceived a difference between online and offline contexts and these responses were subject to thematic analyses. Two themes were identified: the Features and Affordances of Online Contexts (including control, non-verbal cues, and accessibility), and the Nature of Interactions across contexts (including the depth, intimacy, and perceived value of interactions). The current findings highlight the potential for individual characteristics to shape online experiences and are discussed in light of implications for friendship closeness in the digital era.